Application of FAHP–PROMETHEE Hybrid Model for Prioritizing SMEs Failure Factors. Issue 3 (3rd July 2021) - Nikolić, Nenad; Nikolić, Djordje; Marinkovic, Sanja; Mihajlovic, Ivan
Abstract: There is no doubt that small and medium-sized enterprises (SMEs) play a significant role in the economy of one country. The aim of this paper is to rank SMEs failure factors in order to identify the most influential ones. Identification of the most influential factors can help SMEs develop an optimal strategy for improving a business environment and remove obstacles they encounter while conducting business. In addition, the existing and future entrepreneurs/managers would become aware of potential obstacles. Therefore, they would be able to prepare an appropriate response to overcome these obstacles. For the ranking of the failure factors of SMEs, the hybrid Fuzzy Analytic Hierarchy Process (FAHP)–Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) model was used, which represents a new approach to ranking of the failure factors. The ABC method was applied to the obtained results in order to separate the group of the most influential factors. This group includes the following factors: Economic issues, Possibility of increasing capacity, Political issues, the Supply of electricity, Management of receivables/payables and Legislative issues. The obtained results indicate that the main problems which SMEs encounter come from the environment in which they operate, as well as from SMEs themselves. Therefore, there is an additional need to improve the business environment for SMEs, and also to identify these factors and resolve the problems in order to reduce the potential SMEs failure.